The failures of flexible couplings due to self-heating by torsional vibrations – validation on the heat generation in pneumatic flexible tuner of torsional vibrations. (January 2021) - Krajňák, Jozef; Homišin, Jaroslav; Grega, Robert; Kaššay, Peter; Urbanský, Matej
Highlights: Failures of elastic elements of flexible coupling. Impact of vibrations on thermodynamic conditions in the pneumatic tuner. Experimental verification of vibrations impact on produced of temperature fields. Simulation model of vibrations impact on the heat generation and transfer. Abstract: The phenomenon of torsional vibrations which arise in mechanical systems has become an important issue in mechanical design. Flexible couplings are widely used to tune dynamic proproperties of systems and suppress torsional vibrations. Elastic elements in flexible couplings have traditionally consisted of rubber or metal springs. Torsional vibrations cause self-heating of elastic elements. Temperature increase of elastic elements is often a cause of failure of flexible couplings. Our research is focused on the application of pneumatic elastic elements in flexible couplings. Their use in rotational systems brings about numerous design challenges. The properties of pneumatic elastic elements are affected by multiple factors such as excitation frequency and amplitude, the state of prestress, various types of deformations, etc. Heat generation and temperature increase due to the deformation of the pneumatic elastic element can have a significant effect on its properties. A mathematical model of the thermodynamic processes taking place in the pneumatic elastic elements is developed. The theoretical predictions are verified by experiments on a testing rig which has been designed and manufactured for this purpose. Comparing the mathematical model with experimental results, we describe the evolution of temperatures within the system: the temperature of the enlosed air, the inner surface, and outer surface of the pneumatic elastic element.